Implementasi Festival Anak Ceria Berbakat sebagai Wadah Pengembangan Minat dan Bakat Anak - Salamuddin, Salamuddin; Dlt, Kurnia Rizky; Rahayu, Widya; Hasibuan, Dinda Lestari; Pasaribu, Pardamean Halomoan; Hasibuan, Rohima Rizky (Yayasan Inspirasi El Burhani, 2025)
Introduction: The Festival Anak Ceria Berbakat (FACB) is part of the TAO I-LAND UINSU 2025 community service program conducted in Gunung Tua Julu Village. The activity was designed as a platform to nurture children’s talents and interests through educational, religious, and recreational events. It emerged from the community’s need for a creative and constructive space that fosters self-confidence, creativity, and positive character development among children. Objective: This study aims to describe the implementation process of FACB as a medium for developing children’s potential in rural areas, to assess community participation, and to identify the festival’s impact on children’s confidence, skills, and social attitudes. Method: A qualitative descriptive method was employed through observation, interviews, and documentation during the festival. The participants included KKN student organizers, village officials, parents, and children. Data were analyzed descriptively to provide a comprehensive picture of the planning, implementation, and outcomes of the activity. Result: The results showed that the FACB received strong enthusiasm from both children and the community. Various competitions, such as Qur’an recitation, adzan calling, fashion show, Islamic speech (pildacil), quiz contests, and coloring activities, served not only as entertainment but also as a medium for moral, religious, and emotional education. The program successfully enhanced children’s creativity, social interaction, and confidence, while fostering stronger community engagement. Conclusion: The implementation of FACB demonstrates that community service programs can effectively empower local communities and build children’s character, religiosity, and creativity. This initiative provides a practical example of how collaboration among students, educational institutions, and communities can create meaningful and sustainable educational spaces for rural child development.